Role of pharmacist during COVID-19 pandemic: A retrospective study focused on critically ill COVID-19 patients - Abdulrahman Alwhaibi; Abdulmohsin Alrwaished; Shoug Majed Binobydaan; Sawsan Alawwad; Syed Wajid; Salmeen Bablghaith; Sultan Alghadeer; Mohammed N Al Arifi (Elsevier, 2021)
Background and aim: During the Coronavirus 2019 (COVID-19) crisis, there has been a huge demand for medications and unprecedented utilization of intensive care unit (ICU) services that subsequently and profoundly impacted the quality of medical care provided to COVID-19 patients. This study aimed to shed light on the role of pharmacists on the health care provided to critically ill COVID-19 patients. Methods: A retrospective study, was conducted in Diriyah hospital in Riyadh, Saudi Arabia on all COVID-19 patients admitted to the ICU between June 27th and August 15th, 2020 until patients were transferred to the medical ward, discharged, or deceased. All medication related interventions performed by pharmacists have been documented electronically, collected and subsequently categorized and analyzed. Results: The mean age of patients was 58.8 years (±12.98 SD), with age of >64 years in approximately 37%. Four hundred and seventy interventions (470) were made by pharmacists of which 32%, 11.7%, 4%, 2.6%, 2.1% were due to error in dosing regimens, drug duplication, missing drug information, drugs requiring prior authorization, and missing critical information, respectively; while 40.6% were due to medication shortage of which 40.3% were substituted with alternative medications. Based on the analysis of drugs involved in interventions, medication groups that were mainly associated with interventions included antibiotics (16.8%), electrolytes/minerals (11.7%) and vitamins (9.4%). Conclusion: During health crises such as COVID-19 pandemic, the role of pharmacists in the ICU services becomes extremely crucial for providing better patients' outcomes. Further studies should be conducted to follow up these findings in the context of COVID-19 pandemic.